ANALISIS KONDISI MESIN PERKAKAS BUBUT BEMATO 1224BV DI LABORATORIUM POLMAN BABEL MENGGUNAKAN CONDITION BASED MONITORING - Noermala atika sari Tika; Indra Feriadi; Angga Sateria (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Bangka Belitung state manufacturing polytechnic is one of the public universities that there are many tooling machines. One of the tooling machines located in the babel polman laboratory is a bemato type 1224BV lathe tooling machine that will be researched with condition based monitoring methods. In this study, the authors have done data on the accuracy of geometry, checking the viscosity of lubricants, checking automatic feeding eaters and checking vibrations on spindles. In each of the studies that have been done on average has experienced irregularities. The results found in this study are deviations in geometric accuracy by 47%, viscosity that has passed ISO VG by 27%, eaters on automatic feeding by 33% and vibrations in spindles by 33%. The conclusion obtained in this study is the annihilation that occurs in lathes whether the deviations that have occurred in the tooling machine are too far from the permissible limit with the aim of establishing the tightening of the maintenance scheduling system on the lathe machine using the condition based monitoring method.